A new aminoglycoside etimicin shows low nephrotoxicity and ototoxicity in zebrafish embryos. Issue 7 (22nd October 2020) - Shao, Weihao; Zhong, Dan; Jiang, Haowei; Han, Yujie; Yin, Yu; Li, Ruining; Qian, Xiuping; Chen, Daijie; Jing, Lili
Abstract: Aminoglycoside antibiotics are widely used for many life‐threatening infections. The use of aminoglycosides is often comprised by their deleterious side effects to the kidney and inner ear. A novel semisynthetic antibiotic, etimicin, has good antimicrobial activity against both gram‐positive and gram‐negative bacteria. But its toxicity profile analysis is still lacking. In the present study, we compared the in vivo toxic effects of three aminoglycosides, gentamicin, amikacin, and etimicin, in zebrafish embryos. We examined the embryotoxicity, nephrotoxicity, and the damage to the neuromast hair cells. Our results revealed that etimicin and amikacin exhibit more developmental toxicities to the young embryos than gentamicin. But at subtoxic doses, etimicin and amikacin show significantly reduced toxicities towards kidney and neuromast hair cells. We further demonstrated that fluorescently conjugated aminoglycosides (gentamicin‐Texas red [GTTR], amikacin‐Texas red [AMTR], and etimicin‐Texas red [ETTR]) all enter the hair cells properly. Inside the hair cells, gentamicin, not etimicin and amikacin, displays robust reactive oxygen species generation and induces apoptosis. Our data support that the different intracellular cytotoxicity underlies the different ototoxicity of the three aminoglycosides and that etimicin is a new aminoglycoside with reduced risk of nephrotoxicity and ototoxicity. Abstract : The toxic effects of a new aminoglycoside antibiotic etimicin were examined in zebrafish embryos and compared with those of gentamicin and amikacin. Etimicin and amikacin demonstrate reduced nephrotoxicity and ototoxicity than gentamicin. The neuromast hair cell uptake of three drugs is similar, but only gentamicin induces reactive oxygen species (ROS) generation and apoptosis in the cells. The data support that the different intracellular cytotoxicity underlies distinct ototoxicity and that etimicin is a new aminoglycoside with reduced nephrotoxicity and ototoxicity.